(untitled) (Journal of Applied Learning and Teaching, 2025)
In Transnational Higher Education, which encompasses teaching and learning across national borders, the necessary qualities, skills, and knowledge for educational leaders have transformed to meet changing international contexts (Morris et al., 2024). This interview considers some of these aspects from the perspective and experiences of a very experienced academic leader in higher education. James Trotter, featured in this interview, discusses his experiences from a successful career spanning over thirty years in higher education from which he retired in September 2024, and which included in the last decade an academic leadership role of spearheading an offshore transnational university campus. Dr. Trotter provides advice from a journey which started off as a teaching role to becoming a leader in academia. The interview also highlights the increasing importance of the transnational education sector in the context of higher education, of being an academic leader in a multicultural transnational higher education context and grappling with the challenges of working as a leader in a transnational context, especially ones such as Artificial Intelligence and its impacts on education.